Explaining self-reported financial security among seniors - Andrew G. Biggs; Giorgi Bokhua (American Enterprise Institute (AEI), 2024)
Retirement income adequacy is front of mind, both for households preparing for old age and for policymakers seeking to assist them in doing so. Yet there is a central contradiction in the minds of both: while majorities seem convinced that most Americans undersave for retirement, retirees themselves describe their financial lives in overwhelmingly positive terms. Some commentators worry that seniors may be overstating their levels of financial security. We seek to resolve these questions using data from the Federal Reserve Board's Survey of Household Economics and Decision making. We find that retirees, on average, report significantly better financial well-being compared to the working-age population. Senior's higher levels of self-reported financial security are supported by objective measures of financial security, such as the ability to pay all bills, afford necessary medical services, and maintain emergency funds for rainy days, where retirees consistently perform better. These factors, rather than age or retirement status alone, also appear sufficient to explain the differences in reported financial well-being, suggesting that seniors are not more likely to exaggerate their levels of financial security.
Keywords: 330